PENGARUH PEMAHAMAN DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN PAJAK PELAKU USAHA KECIL DI KOTA BANDUNG - ramdani, - (2020)
The purpose of this study was to determine the effect of understanding and awareness of taxation on tax compliance of small business actors in the city of Bandung. This research uses descriptive quantitative verification method. The analytical method used is multiple linear regression analysis. The sample in this study amounted to 94 respondents who have criteria for the type of food and beverage business and have a turnover of Rp. 300,000,000 - Rp. 2,500,000,000 per year. The results of this study indicate that the understanding of taxation and tax awareness affects the tax compliance of small business actors in the city of Bandung, both partially and simultaneously.